Synthesis and Characterization Studies of ZnSe Quantum Dots - Senthilkumar1, K.; Kalaivani2, T.; Kanagesan2, S.; Balasubramanin3, V. (Asian Journal of Chemistry, 2013)
ZnSe quantum dots have been synthesized by wet chemical, template free process by zinc acetate and elemental selenium powder in presence of ethylene glycol, hydrazine hydrate and a defined amount of water at 90 ºC. The product was in strong quantum confinement regime, having yield as high as 50 %. The transmission electron microscopy (TEM) image indicated that the particles were well dispersed and spherical in shape. The X-ray diffraction (XRD) analysis showed that the ZnSe nanoparticles were of the cubic structure, with average particle diameter of ca. 3.50 nm. The FTIR characteristic indicates that the N2H4 molecule has intercalated into the complex and formed a molecular precursor.